Vol.1 PAPERBACK (Baltic International Yearbook of Cognition, Logic and Communication, 2005)
Table of contents of The Baltic International Yearbook of Cognition, Logic and Communication, volume 1. Published on paper medium (University of Latvia Press, 2005)